Niger : Joint Staff Assessment of the Poverty Reduction Strategy Paper Progress Report. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2003)
The first progress report of the government of Niger on the implementation of the Poverty Reduction Strategy Paper (PRSP) covers the period January 2002 to June 2003. The implementation of the PRSP has been broadly satisfactory since January 2002, and the report provides a candid review of developments in this regard. The report emphasizes the participatory approach and activities that have been used to reinforce the ownership of the strategy by the population. Real GDP grew at an average annual rate of 5.0 percent in 2001-02.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet